Assessment of regional cerebral blood flow in patients with early and late onset alcohol dependence: SPECT study - Erdoğan, Esin; Vardar, Erdal; Durmuş Altun, Gülay; Fırat, Mehmet Fatih (Journal of Surgery and Medicine, 2018)
Aim: Alcohol dependence has negative effects on the structure and functionality of the brain. The age of onset of alcohol is an important parameter in the grouping of alcoholics. The aim of this study is to compare whether regional cerebral blood flow (r-CBF) values differ between early (EO) versus late onset (LO) alcoholic patients. Methods: A total of 33 male patients with alcohol dependence as per DSM-IV criteria and 13 healthy controls were enrolled for the study. Regional measures of cortical cerebral blood flow were assessed using a high resolution Tc-99m-HMPAO single photon emission computed tomography (SPECT). Alcoholic subjects were divided into two groups according to onset of problematic alcohol drinking age. Results: When three groups were compared, r-CBF differences were obtained in inferior frontal, inferior temporal, inferior left occipital and middle left frontal regions. Decreased r-CBF values were found in LO group when they compared to controls in both lower frontal and temporal regions (p<0.05). LO group showed significant reduced r-CBF values in regions of inferior frontal and temporal, inferior left occipital and middle left frontal when compared with EO. Conclusion: Our findings revealed that, there were differences in r-CBF values in EO and LO alcoholics at early abstinence period. These findings suggest that frontal lobes have a key role in alcoholism neurobiology, as noted in previous studies. Repeating the measurements after a long-term abstinence will be useful in revealing differences among the alcoholic groups.